Chlorophyllin Inhibits Mammalian Thioredoxin Reductase 1 and Triggers Cancer Cell Death - Shibo Sun (MDPI AG, 2021)
Food colorants are widely used by humans in food production and preparation; however, their potential toxicity requires an in-depth analysis. In this study, five out of 15 commercial food colorants, namely, lutein, betanin, caramel, crocin and chlorophyll, significantly inhibited wild type selenoprotein thioredoxin reductase 1 (TrxR1, TXNRD1) in vitro. The hyperactive Sec498 residue of TrxR1 was targeted by those five colorants, which was confirmed by the site-directed mutagenesis of TrxR1. Furthermore, two colorants, chlorophyll and betanin, triggered the oligomerization of TrxR1. A chlorophyll-derived compound, chlorophyllin, irreversibly inhibited the 5,5′-dithiobis-2-nitrobenzoic acid (DTNB) reducing activity of TrxR1 with Kinact = 6.96 × 10−3 ± 0.49 × 10−3 µM−1 min−1. Moreover, chlorophyllin reduced the cellular TrxR activity, leading to reactive oxygen species (ROS) accumulation and, subsequently, promoting cancer cell death. In conclusion, this study might contribute to understand the food safety of commercial colorants and provide chemotherapeutic compounds by targeting TrxR1.